Changes in college demography and employment: new challenges for career counselors - Loureiro, Nazaré (2009)
According to official data (GPEARI, 2008), the major proportion of unemployed graduates in Portugal, are female (70.9%) and live in the depressed north region of the country (41.3%). The same report shows an increase of 54% in the attendance of college courses, over the last ten years. This is especially true, for master and PhD courses and for women. In this context, this study aims to evaluate the effects of two forms of a Personal Career Management Seminar (PCMS, forms A and B; Taveira et al., 2006) designed to help graduates and PhD students’ career exploration during the intermediate years of their programs. Treatment and comparison subgroups of graduation and PhD programs, from a north-western university, were administered a pre- and a post-test measure (CES, Stumpf, Colarelli & Hartman, 1983). Analyses of covariance of the difference between post-and pre-test measures were performed to test differences between those groups and gender, having as covariate the pre-test results.